Autochthonous microorganisms as an alternative for biofertilization of Nicotiana tabacum L. - Brizuela-Fuentes, Lianet; Holguín-Peña, Ramón; Macías, Elio; Ceiro-Catasú, Wilson (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Tobacco is a crop of economic importance in tropical countries; it generates significant income in small agricultural areas. Within the agrotechnical activities that are carried out on this plant, biofertilization with Autochthonous Microorganisms (AM) represents a viable option for production with low inputs. Therefore, the objective of the research was to determine the biofertilizer effect of AM on black tobacco cv. Havana-2000. The experiment was carried out on a farm located in Los Cayos, Yara, Granma, Cuba, during the period November-February/2021. For this, the yield variables and the components were measured in the field. Statistical processing was performed using ANOVA and principal component analysis. The AM recorded four groups of microbes: bacteria (7x1012 CFU.mL-1) Lactobacillus sp. and Rhodopseudomonas sp., the fungi (3x1011 CFU.mL-1) Trichoderma sp., Aspergillus sp. and Penicillium sp., the yeasts (2x1011 CFU.mL-1) Saccharomyces sp. and Candida sp. and the actinomycete Streptomyces sp. (1x1010 CFU.mL-1). In the field, the AM biostimulated between 15 - 82 % of the yield and the components, achieving the best results at the dose of 36 L.ha-1. Finally, the importance of using AM as an organic alternative for tobacco biofertilization is demonstrated.